MODEL STRINGER “ LOOK THINK ACT “TERHADAP KEMANDIRIAN PEREMPUAN KORBAN TRAFFICKING DI BOGOR - Titi Nurhayati; Yohana Wulan Rosaria; Dedes Fitria (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Jandri Community is a group formed around 2004 consisting of women without husbands(divorced or independent widows because they are not married but have family responsibilities,biological children or foster children), aiming to establish friendship among members to exchangeideas for mutual support, other goals are physically and economically independent. This groupconsists of 30 people from backgrounds who have experienced sexual exploitation (prostituted,trafficked by others and those closest to them). This study aims to determine the application of theStringer Look Think Act Model to the independence of women victims of Trafficking in Bogor. Thestudy design uses the Action research design with sequential explanatory mixed methods. Datacollection and analysis of quantitative data in the first stage, then followed by qualitative datacollection in the second stage to strengthen the results of quantitative research. The results showedthat the application of the look model could be used to determine the characteristics ofrespondents. The application of the thought model can be used to analyze the needs ofrespondents. The application of the act model can be used to implement a model that is deemedappropriate to the needs of the respondents. It is recommended that institutions dealing with thehandling of women victims of trafficking use the Stringer Look Think Act model approach toapproach women trafficking victims to explore problems and prevent the transmission of sexuallytransmitted infections and HIV / AIDS using voluntary counselling and testing